Regulation of microRNA miR-197-3p/CDC28 protein kinase regulatory subunit 1B (CKS1B) axis by Circular RNA hsa_circ_0000285 promotes glioma progression. Issue 3 (1st March 2022) - Deng, Tao; Liu, Yang; Yang, Yanlong; Yuan, Leyong; Liu, Fangfang; Wang, Xiaobo; Zhang, Qiuying; Xie, Mingshui
ABSTRACT: Circular RNA circ_0000285 is differentially expressed in several malignancies; however, its role in gliomas is under investigation. Reverse transcription quantitative polymerase chain reaction was conducted to evaluate the expression of circ_0000285, miR-197-3p, and CDC28 protein kinase regulatory subunit 1B (CKS1B) in glioma tissues and cells. Cell Counting Kit-8 and Transwell invasion assays coupled with Western blotting analysis using anti-Bax and anti-Bcl-2 antibodies were performed to evaluate cell proliferation, invasion, and apoptosis. Luciferase reporter and AGO2 RNA immunoprecipitation assays were conducted to verify the interaction between miR-197-3p and circ_0000285 or CKS1B. Xenograft tumor growth was evaluated in mice. We noted that circ_0000285 was highly expressed in glioma tissues and cells and that circ_0000285-silencing retarded tumor growth both in vitro and in vivo. This effect was mediated by the binding of circ_0000285 to miR-197-3p, which silenced CKS1B, an essential driver of glioma cell proliferation and invasion. Thus, circ_0000285 boosted glioma progression by regulating the miR-197-3p/CKS1B axis, highlighting a novel competing endogenous RNA circuit of glioma progression. Abstract: uf0001